Programmes for boys and men: possibilities for gender transformation. Issue 3 (3rd April 2023) - Keddie, Amanda; Hewson-Munro, Shelley; Halafoff, Anna; Delaney, Maria; Flood, Michael
ABSTRACT: The contemporary #MeToo moment has led to renewed concern about issues of masculinity and gender justice. This moment provides a strong warrant for critically analyzing different programmes for boys and men in relation to their capacity for gender transformation. This paper presents three such programmes located in Victoria (Australia) as case studies (1) an Activist Programme, (2) a Sports Programme, and (3) a Rites Programme. The paper highlights some of the possibilities and contentions for each programme in relation to their capacities for gender transformation through comparative analysis. The paper draws attention to the complexity and diversity of 'promising approaches' for effectively engaging boys and men in respectful masculinities.